السلوكات التدريسية لأساتذة التربية البدنية والرياضية للطورين المتوسط والثانوي حسب آداة حمدان لملاحظة وتحليل التفاعل الصفي الشامل. - عبد الحفيظ, قادري (Université de M'sila, 2019)
الملخص: مع تطور المناهج وإستراتجيات وطرق وأساليب التعليم، تطور أيضا دور الأستاذ فلم يعد ناقلا للمعرفة وفقط، بل أصبح موجها وناقدا ومرشدا للمتعلم في كيفية حصوله للمعرفة ذاتيا. والتربية البدنية والرياضية كأحد المواد التدريسية لا تخرج عن هذا الإطار المفاهيمي التدريسي من أجل الوصول إلى مستوى التمكن، والذي يتطلب عملية قياس موضوعي لهذا السلوك أثناء إجراء الحصة، والتي يتفاعل فيها المعلم والمتعلم، هذا القياس الذي يسمح لنا بعملية تقويم لهذا السلوك حتى يمكن تدعيمه، كما يمكن أن نقيم ثم نقوم سلوكات كل من المعلم والمتعلم، وفي هذا الصدد ظهرت أدوات كثيرة خاصة في البيئة العربية حيث صمم محمد زياد حمدان آداته لملاحظة التفاعل الصفي الشامل، ومن خلال تدريس الباحث لسنوات عديدة كأستاذ للتعليم الثانوي ، ثم كأساتذة للتعليم الجامعي لاحظ عدم إهتمام بعض أساتذة التربية البدنية والرياضية لموضوع التفاعل مع المتعلم، كما لاحظا أن الطرق التقليدية في تقييم وتقويم الأستاذ من طرف مفتشي التربية تفتقر لحد ما إلى الموضوعية وإلى برامج إعداد وتكوين أستاذ قادر على التفاعل بفاعلية. ومن أجل تحقيق أهداف البحث تم القيام بدراسة إستطلاعية بحضور بعض حصص التربية البدنية والرياضة للطورين الدراسيين بدائرة بريكة خلال الموسم الدراسي 2017-2018، كان الهدف منها معرفة ميدانية للسلوكات التدريسية التي تحدث في حصص التربية البدنية و الرياضية للطورين المتوسط و الثانوي. وقد تم إستخدام المنهج الوصفي عن طريق ملاحظة منتظمة للسلوك التدريسي بين الأستاذ و التلاميذ. ومنه إختيار عينة بطريقة قصدية من أساتذة التربية البدنية و الرياضية وعينة من التلاميذ للطورين المتوسط و الثانوي قصد تطبيق الأداة عليها، كما تم الإستعانة بحساب النسبة المئوية للفئات السلوكية المميزة لآداة حمدان. من خلال عرض النتائج و مناقشتها تم التوصل إلى: أظهرت الدراسة صلاحية إتباع نظام حمدان في ملاحظة التدريس وتقويمه في حصص التربية البدنية والرياضية. تختلف أنماط التفاعل اللفظي من أستاذ لآخر مع وجود فروق في النسب بالمقارنة مع نسب حمدان في بعض الفئات. الأستاذ ذو الخبرة تغلب عليه السلوكات التالية: مديح وتشجيع التلاميذ- قبول وإستعمال أفكار التلاميذ - إعطاء الأوامر والتوجيهات- إستجابة التلاميذ -مبادرات التلاميذ-الهدوء البناء. في حين الأستاذ قليل الخبرة تغلب عليه الفئات السلوكية التالية: -إعطاء الأوامر و التوجيهات - إستجابة التلاميذ -مبادرة التلاميذ- نقد المعلم لتلاميذه وتبريره لسلطتة. أستاذ التعليم المتوسط تغلب عليه الفئات السلوكية التالية: - إعطاء الأوامر و التوجيهات- نقد المعلم لتلاميذه وتبريره لسلطتة - سلوك المعلم العدائي- مبادرات التلاميذ- أستاذ التعليم الثانوي تغلب عليه الفئات السلوكية التالية: قبول المشاعر - قبول وإستعمال أفكار التلاميذ - إعطاء الأوامر و التوجيهات-إستجابة التلاميذ -مبادرة التلاميذ . الكلمات الأساسية: السلوكات التدريسية ؛ التربية البدنية والرياضية ؛ آداة حمدان للتفاعل الصفي الشامل. Instructional Behavior of Teachers of Physical Education and Sports for the Intermediate and Secondary Schools by Hamdan Tool to Observe and Analyze the Overall Class Interaction. A descriptive study of some of the averages and secondary levels of the municipality of BARIKA - Batna. Prepared by: 1- Abdel-Hafid Kadri, Lecturer, Department B, ISTAPS, University Batna 02. Abstract: With the development of curricula, strategies, methods and methods of education, the role of the professor has also developed and is no longer a mere conveyor of knowledge, but has become a guide, critique and guide for the learner in how to acquire self-knowledge. Physical education and sports as a teaching material do not deviate from this conceptual framework in order to reach the level of mastery, which requires an objective measurement of this behavior during the course of the lesson, in which the teacher and learner interact. This measurement allows us to evaluate this behavior so that it can be strengthened, We can evaluate and then conduct the behaviors of both the teacher and the learner, and in this regard, many tools emerged especially in the Arab environment, where Muhammad Ziad Hamdan designed his instruments to observe the overall classroom interaction, and through the results of many studies the lack of interest of some professors of physical education and sports Interaction with the learner, and also traditional in the assessment and evaluation professor by education inspectors lacked ways to reduce the objectivity and the preparation and composition professor programs Able to interact effectively. In order to achieve the objectives of the research, an exploratory study was conducted in the presence of some physical education and sports classes for the two classes in the Barika class during the 2017-2018 academic year. The aim was to know the field of the pedagogic behavior in the physical and sports education classes for the intermediate and secondary schools. The descriptive approach was used by regular observation of teaching behavior between teacher and students. A sample was chosen from the teachers of Physical and Mathematical Education and a sample of students for the intermediate and secondary schools to apply the tool to them. The percentage of the behavioral categories of the Hamdan tool was also calculated. Through the presentation and discussion of the results, it was reached: * The study showed the validity of the Hamdan system in teaching observation and evaluation. * The patterns of verbal interaction differ from one teacher to another with differences in ratios compared to Hamdan's ratios in some categories. * The experienced professor is overcome by the following behaviors: praise and encouragement of students - acceptance and use of pupils' ideas - giving orders and directions - student response - student initiatives - constructive calm. *While the less experienced professor is overcome by the following behavioral categories: - Giving orders and directions - Students 'response - the pupils' initiative - Criticism of the teacher to his students and justification for his authority. * Professor of intermediate education is overcome by the following behavioral categories: - Giving orders and directions - Criticism of the teacher to his students and justification for his authority - Behavior of the teacher hostile – *Professor of secondary education is overcome by the following behavioral categories: Acceptance of feelings - Acceptance and use of student ideas - Giving orders and directions - Student response - the initiative of pupils. Key words: Teaching behaviors; physical and sports education; Hamdan tool for comprehensive classroom interaction.
Keywords: السلوكات التدريسية ؛ التربية البدنية والرياضية ؛ آداة حمدان ؛ التفاعل الصفي الشامل.